Simulation of the Advection Process of Stokes Flow Inside a Rectangular Cavity Under Constant Velocities - Valentyn Sobchuk; Oleksandr Kurylko; Oleksandr Boryseiko; Oleh Perehuda; Iryna Lebedyeva; Igor Ulitko; Olena Vashchilina (Axioms)
A two-dimensional periodic Stokes flow of viscous incompressible fluid in a rectangular cavity with constant velocities applied to the top and bottom walls is considered. The study of advection regimes is reduced to the sequential solving of two problems. To solve the first problem, the analytical method of superposition, which allows one to obtain any desired accuracy of the velocity field, is used. To solve the second problem, which is associated with obtaining the trajectories of individual fluid particles, numerical calculations of the Cauchy problem were performed. An analysis of the boundary conditions accuracy was performed based on the control of local integration. The advection of the selected volume of fluid in the rectangular cavity under the periodic motion of walls for a finite period time based on piecewise spline cubic interpolation is modeled. The obtained numerical results agree with well-known experimental data.